(3GdJLQjO aj eYGfi cdeI GdJhMjOs - (3CHh GdaJhM CMeO Hf eMeO GdZRGdis
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdTjN GdEeGe LeGd GdESdGe CMeO Hf eMeO Hf eMeO GdZRGdi QMeg Gddg Ydjg (B: (3LGA ai GdMOjK GdUMjM Yf SjO GdHTQ eMeO Ydjg GdSdGe Cfg bGd ENHGQkG Yf Gddg JYGdi bGd ai cdeg GdJhMjO (B: (3dG Edg EdG Gddg MUfi aef ONd MUfi Cefs
(3BNQgG (B:s
(3LYdfG Gddg hEjGce eef ONd MUf Gddg Hefg hcQeg hEMSGfg HOGjI hfgGjI hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B83s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B351s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds